An exploratory study on shopping center trip generation - Ortiz, Gilbert Roland C.
The current boom in shopping center construction entails the usage of some shopping center trip factor. The main objective of this research was to determine these rates. The results were that the observed shopping center vehicle trip rates greatly differed from foreign trip rates. This was due to the fact that 69-80 percent of Filipino shoppers use the bus and jeepney while 90 percent of the foreign shoppers use private vehicle. Due to the lack of samples, no accurate and stable trip prediction multi-linear model was established. As a result thereof, the researcher recommended more samples to be gathered using his formulated survey methodology.
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Shopping center trip